Pedagogical And Psychological Factors Of Preparing Children For School In Preschool Education Organization (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article discusses the problems of preparing children for school, the stages of physical, personal (mental), mental, special preparation of children for school.